The Influence of Job Training, Work Competency, and Job Evaluation on Employee Performance at PT. BPR Bank Jombang Perseroda - Denis Mega Aulia Darmavika; M Sihab Ridwan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine partially or simultaneously namely the independent variables of Job Training, Job Competence, and Job Evaluation with dependent variable Employee Performance at PT. BPR Bank Jombang Perseroda. The method in this study uses the validity test, test reliability and classical assumption test, data analysis was performed by Regression Analysis Multiple Linear and Determination Coefficient Analysis (R²), while technique hypothesis testing using the t test and F test. Job Training partially positive and significant to Employee Performance, Work Competence partially positive but not significant effect on employee performance, research Job Evaluation partially has a positive and significant effect on performance Employee. F test or Simultaneously the variables of Job Training, Work Competency, and Job Evaluation have an effect significant to Employee Performance.